Multiple social identities cloud norm perception: responses to COVID-19 among university aged Republicans and Democrats - Krupka, Erin; Hoover, Hanna; Eckel, Catherine; Rosenblat, Tanya; Ojumu, Oluwagbemiga; Wilson, Rick K. (Frontiers in Behavioral Economics, 2023)
Introduction Most work on social identity, defined as one's sense of self derived from membership to social groups, focuses on a single identity and its behavioral consequences. But a central insight of social identity theory is that people belong to multiple social groups, derive self-esteem from multiple identities and care to conform to the norms for those identities. However, very little work has turned its attention to understanding when and how multiple social identities interact. We motivate hypotheses with a framework that extends a social identity model to include multiple identities. Methods Using a longitudinal sample (N > 600) of university students located primarily in Texas and throughout the US, we use university social identity, and the associated university norms, to characterize COVID related social distancing norms between April and October of 2020 and then unpack how another identity, the student's political identity, impacts perception of those norms. Results Despite incentives to do otherwise, we find that beliefs about university norms differ depending on the respondent's political identity. We interpret this as a spillover effect of attitudes from one identity to another. Discussion We relate our results back to a model of social identity, to the literature on spillovers where such psychological spillovers are hard to empirically identify, and to methods for future work on identity and spillovers.